Pembuatan Video Iklan Untuk Meningkatkan Brand Awareness Pada UMKM Keripik Buah Dan Sayur Pandubima Malang - Nanda Dian Pramesti; Dwi Sudjanarti; Heru Utomo (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
Instagram is one of the digital promotion media widely used by MSMEs; however, the Instagram account of PANDUBIMA Fruit and Vegetable Chips MSME in Malang has not utilized Reels video content, resulting in low brand awareness. This study aims to identify the condition of brand awareness before using advertising videos, produce an advertising video using the CapCut Pro application, and measure its effectiveness in building brand awareness. This study used the Action Research method following the Kemmis and McTaggart model through two cycles consisting of planning, acting, observing, and reflecting, involving 16 respondents consisting of the owner, employee, marketing experts, computer experts, and consumers. Data were collected through interviews, observation, documentation, and an EPIC Model questionnaire analyzed using mean scores and the EPIC Rate. The results show that the initial condition of PANDUBIMA's brand awareness was at the unaware of the brand level. In the second cycle, the expert EPIC Rate increased from 3.08 to 4.76 and the general respondent rate from 4.08 to 4.67, with the overall brand awareness score increasing from 3.89 to 4.67 (Very High category). This study concludes that producing an advertising video using CapCut Pro through the Action Research approach effectively increased PANDUBIMA's brand awareness through Instagram Reels and can serve as a reference for other MSMEs in improving digital marketing effectiveness.